Hur påverkar gummigolv i grisningsboxen suggans liggtider, liggbeteende och hennes tid för att lägga sig? - Winter, Nina (2014)
In the farrowing pens the amount of bedding material and the quality of the concrete floor has a huge impact on both the sow and the piglets. In this study imbedding of rubber flooring on the solid area in the farrowing pen was used to see if it had any effects on the sows lying behaviour when compared to concrete. Another important aspect was to evaluate if the rubber floorings had a high enough durability to resist the normal wear in a farrowing pen. Concrete flooring is assumed to have a higher thermally conductive effect then rubber which can affect the sow’s chance to cool down. Therefore the temperature in the farrowing compartment was measured to see if there was a correlation between the sows lying behaviour and the temperature. In total, the study was performed during five farrowing batches, in total about 30 weeks observation period. In each batch, two “rubber” pens and two “concrete” pens were included in the behavioural observations. Three different rubber floorings were included in the study; ProCoat rubber compound, Porca relax, and KKM Porca prototype. Continuous video recordings for the behavioural observations were made twice during the suckling period of five weeks. The video recordings were 24 hours each and took place at about one and three weeks after farrowing. The different behaviours that were noted were standing/walking, lying on the side, lying on the abdomen and sitting. The floor in the farrowing pen was divided into three different zones: solid flooring, slatted flooring and transition zone between solid and slatted flooring. In the behavioural study there was a significant difference one week after farrowing and a trend three weeks after farrowing, that the sows in the rubber pens lay down less than the sows in the concrete pens. This difference was not due to less lying on the solid floor area in the “rubber” pens, but was due to significantly less lying in the transition zone. In contrary, when only looking at the behaviour lying and recalculating the figures for this there was a weak, but not significant, trend that the sows chose to lie more on the solid rubber area than on the solid concrete area in the pen. The highest mean temperature was 21.9 °C and the lowest mean temperature was 15.1 °C. The assumption that sows could be more sensitive to higher temperatures when on the rubber floor, due to less thermal conductivity, could not be confirmed nor disregarded because the temperature during the observation period did not exceed the sows’ thermo neutral zone (15-20 °C) by much. The relation between temperature and lying percent on the slatted area showed a large variation between individual sows. The time it took for the sows to lie down showed no significant difference between the treatments, but a great variation between individual sows could be noted. The good durability of the Porca relax and of the KKM Porca prototype rubber mats were convincing during the whole study. In contrast ProCoat rubber flooring did not sustain the tough rooting behaviour of a sow in a farrowing pen and broke down. In conclusion there were large individual variations in sow behaviour in the study and the sows, in the farrowing pens, choose between different surfaces with different thermal and comfort properties. The use of rubber flooring instead of concrete on the solid area in the farrowing pen did not seem to be a great advantage in this herd. But the study showed that there are now rubber mats on the market, which can sustain the weight and behavioral activity of sows.